2021
DOI: 10.1021/acs.jpclett.1c00223
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Mechanism for the Initial Myosin Binding Event on the Cardiac Thin Filament: A Metadynamics Study

Abstract: The movement of tropomyosin over filamentous actin regulates the cross-bridge cycle of the thick with thin filament of cardiac muscle by blocking and revealing myosin binding sites. Tropomyosin exists in three, distinct equilibrium states with one state blocking myosin–actin interactions (blocked position) and the remaining two allowing for weak (closed position) and strong myosin binding (open position). However, experimental information illuminating how myosin binds to the thin filament and influences tropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Generation of computational cTF models for calcium-depleted (−Ca 2+ ) and calcium-saturated (+Ca 2+ ) thin filaments follows a similar procedure utilized previously. 47 Our previous computational cTF model 51 was refined according to recently published cryo-EM images of the cTF that demonstrated the orientation of the cTn core within the cTF thin filament and the organization of cTnT within the overlap region. 10 This previous model differs from the recent cryo-EM structures in the placement of the TnT helix within the overlap region of the thin filament and the orientation of the Tn core.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generation of computational cTF models for calcium-depleted (−Ca 2+ ) and calcium-saturated (+Ca 2+ ) thin filaments follows a similar procedure utilized previously. 47 Our previous computational cTF model 51 was refined according to recently published cryo-EM images of the cTF that demonstrated the orientation of the cTn core within the cTF thin filament and the organization of cTnT within the overlap region. 10 This previous model differs from the recent cryo-EM structures in the placement of the TnT helix within the overlap region of the thin filament and the orientation of the Tn core.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Structures utilized in this study were created starting from the cryo-EM structures published by Yamada, Namba, and Fujii, as previously described, , which provided structures for both Ca 2+ -saturated and -unsaturated conformations of the CTF (PDB 6KN8 and 6KN7, respectively). In the context of saturation of the CTF, a fully saturated system refers to Ca 2+ bound to site II of cTnC, while unsaturated refers to no Ca 2+ bound to site II of cTnC.…”
Section: Methodsmentioning
confidence: 99%
“…All structured fragments were aligned and the proteins were subjected to minimization until all bonds and angles were acceptable values. Any clashing of proteins was resolved by rotating dihedral angles in the unstructured regions, as previously described. , The helical pitch of Tm in the Yamada structure was corrected to agree with the protein docking study by Pavadai et al, allowing Tm to span 7 actin monomers instead of the 6 monomers in the original pdb. The structure for the cTnI C-terminal domain of the Ca 2+ -unsaturated state was also corrected to agree with the docking study by Lehman et al, which found a more energetically favorable location compared to the originally published structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations